Impact of Eco-Friendly Practices on Resort Profitability in the Maldives - Riyaz, Ahmed (International Journal of Modern Hospitality and Tourism, 2024)
Purpose: The aim of the study was to analyze the impact of eco-friendly practices on resort profitability in the Maldives. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Studies on the impact of eco-friendly practices on resort profitability in the Maldives show that sustainable practices, such as renewable energy use, water conservation, and waste reduction, positively affect profitability. Resorts adopting green initiatives benefit from lower operational costs, such as reduced energy and water consumption, while also attracting environmentally conscious tourists willing to pay premium prices. These practices also enhance brand reputation and long-term resilience, reducing dependency on finite resources. However, the initial investment in eco-friendly infrastructure can be high, and profitability gains are more evident in the long term. Unique Contribution to Theory, Practice and Policy: Sustainable tourism theory, corporate social responsibility (CSR) theory, resource-based View (RBV) theory may be used to anchor future studies on the role of technological advancements on customer satisfaction in Japan’s hospitality. Practically, resorts in the Maldives can use this research to improve their profitability while simultaneously enhancing their environmental sustainability. At a policy level, this research can provide empirical evidence for policymakers in the Maldives to promote and regulate eco-friendly practices in the tourism sector.